Exploring the Relationships of Grading Assessment Learning Perceptions Scales to Perceived Added Education Value Required Course Business Scales (Journal of Education and Development, 2020)
This study’s purposes were to: develop added education value required business course scales; and investigate their relationships to four grading assessment learning perception (GALP) scales. Using a sample of spring, 2018, n = 944, graduating business undergraduates, three reliable (coefficient alpha) added education value required business course scales were identified: Lower-level Foundation (.92), Business Administration (.88), and Quantitative (.84). The Quantitative scale had a higher perceived added education value (Mean, M = 4.38 out of 6), versus Lower-level Foundation (M = 4.22), and Business Administration (M = 3.97). However, the relationships for three of the four GALP scales, i.e., exam, individual engagement, and team, were significantly stronger to the Business Administration scale, and the average correlation (r) across all GALP scales was higher to the Business Administration scale (r = .36) versus the Lower-level Foundation (r = .28) and Quantitative (r = .20) scales. Part of curriculum assessment should involve measuring the perceived added education value of each required course, in any school or college, not just business. This can represent a significant portion of a student’s investment in a degree. It is hoped that this study will stimulate continued research on the development of added education value scales.